Allomaieta isauroi (Melastomataceae, Cyphostyleae): a new species from the Andean-Amazonian Foothills of Colombia - Murillo-Serna, Jhon S.; Trujillo-Trujillo, Edwin; David-Higuita, Heriberto A.; Perdomo, Oscar; Mendoza-Cifuentes, Humberto (Phytotaxa, 2025)
Allomaieta isauroi, a new species of Melastomataceae (Cyphostyleae) is described and illustrated. The new taxon is only known from the Andean-Amazonian foothills on the eastern slopes of the Eastern Cordillera of the Colombian Andes. This is the second species described in this area, and it can be distinguished from the other previously described species by the combination of leaf blades with one pair of suprabasal, secondary veins plus a marginal pair, turbinate flower buds, petals light pink basally white, and apically obtuse anthers. Allomaieta isauroi has a restricted distribution and is endangered due to habitat loss.